Surface and electrochemical characterization of boron-doped diamond electrodes prepared under different conditions - Šelešovská, Renáta; Štěpánková, Michaela; Janíková, Lenka; Nováková, Kateřina; Vojs, Marián; Marton, Marián; Behúl, Miroslav (My University, 2016)
In this study, physical, chemical, and electrochemical properties of lab-made boron-doped diamond electrodes (BDDE) prepared by hot filaments chemical vapor deposition under different conditions have been investigated. The B/C ratio in the gas phase varied in the range of 0–20,000 ppm and the content of CH4 in H2 was changed in the interval of 0.5–2 %. Scanning electron microscopy and Raman spectroscopy were used for characterization of BDD films. Cyclic voltammetry and electrochemical impedance spectroscopy of the redox system [Fe(CN)6] 3-/4- were used for electrochemical characterization of prepared electrodes. Finally, all BDDEs in combination with differential pulse voltammetry were tested for herbicide linuron determination under optimized experimental conditions.
Povrchová a elektrochemická charakterizace Borem dopovaných diamantových elektrod připravených při různých experimentálních podmínkách
Keywords: Boron-doped diamond electrode; Scanning electron microscopy; Raman spectroscopy; Voltammetry Electrochemical impedance spectroscopy; Linuron; Borem dopovaná diamantová elektroda; Skenovací elektronová mikroskopie; Ramanova spektroskopie; Voltamertie; Elektrochemická impedanční spektroskopie; Linuron